POTENSI SIANIDIN POLY(LACTIC-CO-GLYCOLIC ACID)-POLYETHYLEN GLYCOL YANG DIMODIFIKASI FUSED FOLLICLE UNTUK MENINGKATKAN SENSITIVITAS DAN SEKRESI INSULIN DALAM MENANGANI PENYAKIT DIABETES MELITUS TIPE 2 - Gorintha, Adrian Wiryanata; Debora, Stevina; Chandra, Natasya Eiffeline (Essence of Scientific Medical Journal; Vol 20 No 1 (2022): Volume 20 No. 1 (Januari - Juli 2022) Essential: Essence of Scientific Medical Journal, 2022)
ABSTRACT Introduction: Type 2 diabetes mellitus is one of the four priority non-communicable diseases according to WHO. WHO data in 2015 showed that as many as 415 million people in the world suffer from type 2 diabetes mellitus. Even in Indonesia in 2013, the prevalence of people with diabetes has increased to 6.9%. Currently, the most common treatment for type 2 diabetes mellitus is the administration of metformin. However, long-term administration will cause lactic acidosis and kidney damage. Because of this, new alternatives are needed that minimize the side effects, for example by using herbal ingredients. Cyanidin is a natural flavonoid that has the effect of increasing insulin sensitivity and secretion.   Discussion: Cyanidin has the potential to increase insulin receptor sensitivity and increase insulin secretion. To increase insulin sensitivity, cyanidin can inhibit the downregulation of Glut4 expression and decrease the level of RBP 4 expression. As an increase in insulin secretion Cyanidin increases the expression of GLUT2, Kir6.2, and Cav1.2 genes that play a role in insulin secretion. Unfortunately, Cyanidin has low bioavailability and is unstable. Therefore, Cyanidin encapsulation will increase the availability of cyanidin in the blood and is easily concentrated into pancreatic cells Conclusion: The Fc-modified Cyanidin PLGA-PEG combination has the potential to be a new alternative in the treatment of type 2 diabetes mellitus Keywords: Type 2 Diabetes Mellitus, Cyanidin, Fc-modified Cyanidin PLGA-PEG